Identification of LIMK2 as a therapeutic target in castration resistant prostate cancer. (28th April 2019) - Nikhil, Kumar; Chang, Lei; Viccaro, Keith; Jacobsen, Max; McGuire, Callista; Satapathy, Shakti R.; Tandiary, Michael; Broman, Meaghan M.; Cresswell, Gregory; He, Yizhou J.; Sandusky, George E.; Ratliff, Timothy L.; et al.
Abstract: This study identified LIMK2 kinase as a disease-specific target in castration resistant prostate cancer (CRPC) pathogenesis, which is upregulated in response to androgen deprivation therapy, the current standard of treatment for prostate cancer. Surgical castration increases LIMK2 expression in mouse prostates due to increased hypoxia. Similarly, human clinical specimens showed highest LIMK2 levels in CRPC tissues compared to other stages, while minimal LIMK2 was observed in normal prostates. Most notably, inducible knockdown of LIMK2 fully reverses CRPC tumorigenesis in castrated mice, underscoring its potential as a clinical target for CRPC. We also identified TWIST1 as a direct substrate of LIMK2, which uncovered the molecular mechanism of LIMK2-induced malignancy. TWIST1 is strongly associated with CRPC initiation, progression and poor prognosis. LIMK2 increases TWIST1 mRNA levels upon hypoxia; and stabilizes TWIST1 by direct phosphorylation. TWIST1 also stabilizes LIMK2 by inhibiting its ubiquitylation. Phosphorylation-dead TWIST1 acts as dominant negative and fully prevents EMT and tumor formation in vivo, thereby highlighting the significance of LIMK2-TWIST1 signaling axis in CRPC. As LIMK2 null mice are viable, targeting LIMK2 should have minimal collateral toxicity, thereby improving the overall survival of CRPC patients. Highlights: LIMK2 was identified as a disease-specific target in CRPC. We show that LIMK2 is upregulated in castrated prostates due to increased hypoxia. Inducible knockdown of LIMK2 fully reverses CRPC tumorigenesis in castrated mice. TWIST1 was identified a direct target of LIMK2. LIMK2 inhibitor shows very high synergy with docetaxel.